Ministry Of Investment and International Cooperation Decree No. 94 Of The Year 2017 Amending Certain Provisions of the Executive Regulations of Law on Joint Stock Companies, Partnerships Limited by Shares and Limited Liability Companies as promulgated by Decree No. 96 of the year 1982 = وزارة الاستثمار والتعاون الدولى قرار رقم 94 لسنة 2017 بتعديل بعض أحكام اللائحة التنفيذية لقانون شركات المساهمة وشركات التوصية بالأسهم والشركات ذات المسئولية المحدودة الصادرة بقرار وزير شئون الاستثمار والتعاون الدولى رقم 96 لسنة 1982 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic